A Review paper on An Efficient Edge Detection and Template Matching based Vehicle Number Plate Recognition (International Journal of Current Engineering and Technology, 2015)
Vehicle number plate recognition is the most interesting and challenging research topic from past few years. It is shown that the number plates are different shape and size and also have different color in different countries. In India the most common vehicle number plate used yellow or white as background and black used as foreground color. In this paper we proposed a system to localization of number plate mainly for the vehicles in West Bengal (India) and segmented the numbers as to identify each number separately. This presents an approach based on simple and efficient morphological operation and sobel edge detection method, template matching. We also presents a simple approach to segmented all the letters and numbers used in the number plate. After reducing noise from the input image we try to enhance the contrast of the binarized image using histogram equalization. Character Recognition of the vehicle plate based on template matching. The simulation result shows that the location is more efficient and effective.
Keywords: Vehicle number plate recognition; character recognition